2021
DOI: 10.1021/acs.est.1c04108
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Microplastic-Associated Biofilm Development along a Freshwater-Estuarine Gradient

Abstract: Microplastic contamination is an increasing concern worldwide. Biofilms rapidly develop on surfaces in aquatic habitats, but the processes of biofilm formation and variation in bacterial community succession on different microplastics introduced into freshwater and estuarine environments are not well understood. In this study, the biofilm bacterial communities that developed on three different types of microplastics that are prevalent in the environment, high-density polyethylene (HDPE), polyethylene terephtha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(15 citation statements)
references
References 42 publications
2
13
0
Order By: Relevance
“…There was no obvious difference between the mass of PFAS on clean and biofouled tubes during concurrent laboratory experiments (Figure ). This could be explained by considering how a thin, high-water-content layer of algae, sponge, or other organic matter (Figure S8) compares to the thick polyethylene membrane in thickness and permeability. , However, biofouling conditions are very difficult to recreate in the laboratory, and the conditioning of these field-exposed tubes likely altered the biofouling layer. Further experiments, such as tube deployments in a laboratory setting with live algae/bacteria, might be necessary to better assess the impact of biofouling on PFAS uptake. …”
Section: Resultsmentioning
confidence: 99%
“…There was no obvious difference between the mass of PFAS on clean and biofouled tubes during concurrent laboratory experiments (Figure ). This could be explained by considering how a thin, high-water-content layer of algae, sponge, or other organic matter (Figure S8) compares to the thick polyethylene membrane in thickness and permeability. , However, biofouling conditions are very difficult to recreate in the laboratory, and the conditioning of these field-exposed tubes likely altered the biofouling layer. Further experiments, such as tube deployments in a laboratory setting with live algae/bacteria, might be necessary to better assess the impact of biofouling on PFAS uptake. …”
Section: Resultsmentioning
confidence: 99%
“…A previous study showed that the dominant MP polymer types in the Haihe River were polypropylene (PP), polyethylene (PE), and polystyrene (PS) . Particles composed of PS, a typical MP polymer, tend to be retained in overlying water because they have low density (0.96–1.05 g/cm 3 ); therefore, they have been widely applied to study the impact of MPs on aquatic systems. , In aquatic systems, the concentration of MPs is <1 mg/L, and the median is 0.1 mg/L . The MP concentration in some rivers and lakes is more than 0.1 mg/L, as listed in Table S3.…”
Section: Methodsmentioning
confidence: 99%
“…Virgin microplastics were obtained by pulverizing plastic boxes that were sieved to produce a fraction of particles with size ranges of 750–1000 μm, which then underwent UV irradiation to create photoaged microplastics (details on the preparation of microplastics are provided in Text S1). The size range was selected based on the dominant occurrence in the natural environment and a previous study on biofilm incubation. , The morphology and chemical components of microplastics are shown in Figure S2. Other reagents are described in Text S1.…”
Section: Methodsmentioning
confidence: 99%
“…The size range was selected based on the dominant occurrence in the natural environment and a previous study on biofilm incubation. 38,39 The morphology and chemical components of microplastics are shown in Figure S2. Other reagents are described in Text S1.…”
Section: ■ Introductionmentioning
confidence: 99%